2004
DOI: 10.2460/javma.2004.225.574
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Salmonella spp from the environment of dairies without any history of clinical salmonellosis

Abstract: Environmental Salmonella contamination was demonstrated on free stall dairies with no history of clinical salmonellosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 13 publications
0
13
1
1
Order By: Relevance
“…10 Peek et al 27 recently reported the isolation of S. Corvallis from the environment of one dairy without any history of clinical salmonellosis. This isolate was also susceptible to all antimicrobial agents tested.…”
Section: Discussionmentioning
confidence: 97%
“…10 Peek et al 27 recently reported the isolation of S. Corvallis from the environment of one dairy without any history of clinical salmonellosis. This isolate was also susceptible to all antimicrobial agents tested.…”
Section: Discussionmentioning
confidence: 97%
“…Salmonella Cerro was also isolated from four dairy herds in Ohio for up to 18 months in the absence of clinical signs; however, three of these herds had experienced clinical outbreaks (diarrhea, abortion, and evidence of endotoxemia) prior to the study period, and Salmonella Cerro was isolated from some of the affected cattle in each instance (Huston et al, 2002a). Salmonella Cerro was isolated from the environment of one Wisconsin dairy farm without a history of salmonellosis, but no cattle were sampled in that study (Peek et al, 2004). The NAHMS Dairy 2007 study, based on a single sampling visit to 121 farms in 17 states, found Salmonella Cerro to be the most common serotype isolated from healthy lactating cows (CEAH, 2009).…”
Section: Figmentioning
confidence: 96%
“…The focus of this study was S. enterica serotype Cerro, an infrequent human pathogen (CDC, 2008) whose role in causing clinical disease in cattle is unclear (Huston et al, 2002a;Peek et al, 2004;Van Kessel et al, 2007). Our objectives were to document the within-herd prevalence of Salmonella Cerro among a sample of dairy herds throughout New York, to describe the antimicrobial resistance patterns and pulsedfield gel electrophoresis (PFGE) types of the Cerro isolates, and to further clarify the status of this serotype as a bovine pathogen.…”
mentioning
confidence: 99%
“…However, asymptomatic fecal shedding of Salmonella has also been well documented (Anderson et al, 2001;Edrington et al, 2004a;Hume et al, 2004;Huston et al, 2002b;Peek et al, 2004). The effect of subclinical endemic infection in a herd is difficult to determine and such research appears not to have been published, but effects on reproduction and milk production are biologically plausible.…”
Section: Introductionmentioning
confidence: 95%
“…(Callaway et al, 2005;Edrington et al, 2004b;Fitzgerald et al, 2003;Hume et al, 2004;Peek et al, 2004). Outbreaks of Salmonella in dairy herds have typically been shown to move through the cattle rapidly although there have been occasional reports of long-term persistence of infection within animals (Giles et al, 1989;Huston et al, 2002a;Radke et al, 2002) as well as in the dairy facilities and in the surrounding environment (Fossler et al, 2005;Peek et al, 2004).…”
mentioning
confidence: 94%